Construction Waste Management from Environmental Law Perspective in Indonesia - Hansen, Seng (International Journal of Law and Public Policy (IJLAPP), 2024)
Several prior studies have linked the relationship between construction activities and environmental degradation. This research focuses on one of the major issues confronting the Indonesian construction industry, namely construction waste management. In practice, construction waste cannot be avoided and thus must be managed properly. Using a descriptive normative legal study approach and a case approach, this research seeks to investigate the practices and conditions of construction waste management as well as the regulatory legal framework related to construction waste management in Indonesia. This study found that the practice of implementing construction waste management varies greatly depending on the understanding and skills of construction business actors, especially contractors and subcontractors. In addition, normative studies show that there is no regulation that specifically regulates the management of construction waste in Indonesia. Therefore, this research contributes by: (1) encouraging the government to make policies that specifically regulate construction waste management, (2) encouraging periodic monitoring and supervision efforts on the implementation of construction waste management, and (3) encouraging the active participation of the community to participate in supervising the execution of construction projects, especially regarding the management of construction waste. Therefore, this study emphasizes the importance of a legal framework for construction waste management in order to realize sustainable construction.